Pemetaan Potensi Batuan Kapur Dengan Memanfaatkan Citra Landsat 8 di Kabupaten Solok - Baihaqi, Yusuf; antomi, yudi (DEPARTEMEN GEOGRAFI FIS UNP, 2026)
This study aims to spatially analyze the potential of limestone in Solok Regency by utilizing image data and GIS (geographical information systems). The output of this research is in the form of information in the form of a limestone potential map, which includes information on the area of ​​high, medium and low potential areas. To determine this potential, 4 parameters were used in the study based on the process of forming karst/karstification areas where limestone can be found, namely vegetation index, geological elements, land cover, and regional geomorphology. This type of research is quantitative descriptive, the data used are Landsat imagery, geological shp, land system and RBI maps with analytical techniques in the form of overlays and scoring. From the data processing, the results obtained are high potential level with an area of 26,365,8 Ha, the medium potential of 140.425 Ha, and the low potential of 150.531 Ha Keywords : Limestone, Solok Regency, Image Data, Geographic Information System